Codon bias confers stability to human mRNAs. (3rd September 2019) - Hia, Fabian; Yang, Sheng Fan; Shichino, Yuichi; Yoshinaga, Masanori; Murakawa, Yasuhiro; Vandenbon, Alexis; Fukao, Akira; Fujiwara, Toshinobu; Landthaler, Markus; Natsume, Tohru; Adachi, Shungo; Iwasaki, Shintaro; et al.
Abstract: Codon bias has been implicated as one of the major factors contributing to mRNA stability in several model organisms. However, the molecular mechanisms of codon bias on mRNA stability remain unclear in humans. Here, we show that human cells possess a mechanism to modulate RNA stability through a unique codon bias. Bioinformatics analysis showed that codons could be clustered into two distinct groups—codons with G or C at the third base position (GC3) and codons with either A or T at the third base position (AT3): the former stabilizing while the latter destabilizing mRNA. Quantification of codon bias showed that increased GC3‐content entails proportionately higher GC‐content. Through bioinformatics, ribosome profiling, and in vitro analysis, we show that decoupling the effects of codon bias reveals two modes of mRNA regulation, one GC3‐ and one GC‐content dependent. Employing an immunoprecipitation‐based strategy, we identify ILF2 and ILF3 as RNA‐binding proteins that differentially regulate global mRNA abundances based on codon bias. Our results demonstrate that codon bias is a two‐pronged system that governs mRNA abundance. Synopsis: Human cells possess a specific mechanism to modulate RNA stability and abundance through a unique codon bias. ILF2/ILF3 heterodimers differentially regulate global mRNA abundances based on this bias. Bioinformatic analyses reveal that codons can be clustered into two distinct groups. Codons have either G or C (GC3) or A or T (AT3) at the third base position. GC3 codons stabilize mRNA, while AT3 codons destabilize mRNA. ILF2/ILF3 heterodimers differentially regulate global mRNA abundances via codon bias. Abstract : Human cells possess a specific mechanism to modulate RNA stability and abundance through a unique codon bias. ILF2/ILF3 heterodimers differentially regulate global mRNA abundances based on this bias.